2017
DOI: 10.1016/j.jeoa.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Redistributive effects of the US pension system among individuals with different life expectancy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, as numerous studies have found, such as Lleras-Muney (2005), Meara, Richards, and Cutler (2008), Bound et al (2015), and Chetty et al (2016), mortality risk tends to decline with education and income. Taking the relationship between income and mortality as given, Sánchez-Romero and Prskawetz (2017), Bagchi (2019), and Bishnu, Guo, and Kumru (2019) each investigate how the progressivity of PAYG Social Security is impacted by differential mortality and show that the progressivity of PAYG systems is negatively impacted by mortality inequality. The general consensus from this literature is that mortality differentials have a significant impact on the economic efficiency of Social Security systems and therefore must be accounted for in the design of such programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, as numerous studies have found, such as Lleras-Muney (2005), Meara, Richards, and Cutler (2008), Bound et al (2015), and Chetty et al (2016), mortality risk tends to decline with education and income. Taking the relationship between income and mortality as given, Sánchez-Romero and Prskawetz (2017), Bagchi (2019), and Bishnu, Guo, and Kumru (2019) each investigate how the progressivity of PAYG Social Security is impacted by differential mortality and show that the progressivity of PAYG systems is negatively impacted by mortality inequality. The general consensus from this literature is that mortality differentials have a significant impact on the economic efficiency of Social Security systems and therefore must be accounted for in the design of such programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This type of pension is also subdivided into: social; loss of a breadwinner; old age; on disability; and for the length of service. The size of the pension is influenced by the length of employment and service, salary, and pension contributions of citizens [49,50].…”
Section: Russiamentioning
confidence: 99%
“…Yet we would argue that no analysis of the links between survival, ageing, and pension expenditures (and, more generally, welfare expenditures) can afford to ignore the differential aspects of the demographic process, as survival varies by gender, social class, and educational level (Caselli et al 2003;Lipsi and Tomassini 2009;Luy et al 2011). Thus, to properly evaluate the redistributive effects of social security and health care policies, it is essential that we study the differential aspects of survival (Bommier et al 2011;Donnelly 2015;Pestieau and Ponthiere 2016;Piggott et al 2005;Sanchez-Romero and Prskawetz 2017).…”
Section: Percentmentioning
confidence: 99%